The Miracle Rising® as source for teaching History: Theoretical and practical considerations (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Twenty years ago, all South Africans – for the first time – had the privilege to vote on an equal basis for the political party to govern the country in the years to come. It was an extraordinary and a momentous phase in the country’s history – a historical milestone indeed. Mr Mandela referred to this occasion as a small miracle. This was undeniably so if one considers that colonial, apartheid, racial and cultural legacies have immensely contributed to divisions, distrust, violence and killings among people of all races and colour. To digestibly capture relics of these memories of reality in a single historical documentary accessible to the ordinary man through the Internet and other media, the producing of Miracle Rising® was and is welcomed in the public domain. To what extent educators of History in South Africa have responded to this documentary since 2012, and have considered using it in History classes, is not known. However, this paper intends to focus on its theoretical and practical value for teaching History that should be embraced in every History class. Teaching Miracle Rising® provides for opportunities to address a very difficult yet jubilant phase in the history of a country so long aspiring for equality and peace. The process leading to South Africa becoming democratic can be regarded as a sensitive topic to teach because of the racist, politically violent and culturally intolerant undertones that occurred decades before the April 1994 election. A maturity with regard to teaching, comprehensive knowledge, as well as an efficient application of teaching skills and assessment techniques will be pivotal in overcoming the moments of sensitivity, especially those captured in Miracle Rising®.
Keywords: History teaching; Teaching democracy; Leadership; Miracle Rising®; South Africa; History documentaries